Economic valuation of collecting water to billing in the aspersion irrigated bean in the no tillage system and conventional crop - Salvestro, Alexandre de Castro; Teixeira Nagaoka, Marilda da Penha [UNESP]; Lemos, Leandro Borges [UNESP]; Tsutsui Esperancini, Maura Seiko [UNESP]; Martins, Carla Maria [UNESP]; Sa, Raquel Andrade; Tavares da Silva, Carolina Amaral; Benetoli da Silva, Tiago Roque (Wfl Publ, 2012)
The law's project n.676/2000 approved the collecting of billing water for farmers in a maximum foreseen value of US$ 0.01 m(-3) of extracted water in the São Paulo State. As the irrigated agriculture is the activity that consumes more water, the farmers profitability can be affected. This work was to analyze the economic impact of billing water in the aspersion irrigated bean crop to consider the system of conventional production and no tillage system in the Paranapanema municipal district, São Paulo State, Brazil. The indicators used to analyze the economic results were unit variable cost, market price and unit profitability. The results showed that for the aspersion irrigated bean crop in conventional system, the participation of cost to the recourse water in cost variable totality was of 2.5% and in no tillage system the participation was of 2.2%. The fall of profitability just the billing water in conventional crop system and in no tillage system was US$ 0.01 kg(-1).
Keywords: Irrigated bean; billing water; economic results